A Cross‐System Comparison of Dark Carbon Fixation in Coastal Sediments. Issue 2 (19th February 2020) - Vasquez‐Cardenas, Diana; Meysman, Filip J. R.; Boschker, Henricus T. S.
Abstract: Dark carbon fixation (DCF) by chemoautotrophic microorganisms can sustain food webs in the seafloor by local production of organic matter independent of photosynthesis. The process has received considerable attention in deep sea systems, such as hydrothermal vents, but the regulation, depth distribution, and global importance of coastal sedimentary DCF have not been systematically investigated. Here we surveyed eight coastal sediments by means of stable isotope probing ( 13 C‐DIC) combined with bacterial biomarkers (phospholipid‐derived fatty acids) and compiled additional rates from literature into a global database. DCF rates in coastal sediments range from 0.07 to 36.30 mmol C m −2 day −1, and there is a linear relation between DCF and water depth. The CO2 fixation ratio (DCF/CO2 respired) also shows a trend with water depth, decreasing from 0.09 in nearshore environments to 0.04 in continental shelf sediments. Five types of depth distributions of chemoautotrophic activity are identified based on the mode of pore water transport (advective, bioturbated, and diffusive) and the dominant pathway of microbial sulfur oxidation. Extrapolated to the global coastal ocean, we estimate a DCF rate of 0.04 to 0.06 Pg C year −1, which is less than previous estimates based on indirect measurements (0.15 Pg C year −1 ), but remains substantially higher than the global DCF rate at deep sea hydrothermal vents (0.001–0.002 Pg C year −1 ). Key Points: Coastal dark carbon fixation rates are highest in diffusion‐driven intertidal areas and lowest in permeable continental shelf sediments Pore water transport and microbial sulfur oxidation mechanisms determine five depth distribution models of dark carbon fixation in sediments The renewal of labile organic matter by dark carbon fixation is important in coastal carbon budgets